The Doctrine of Participation in Abuse of Authority Offenses: Toward Proportional Sentencing in Indonesia's Anti-Corruption Law - Ali Tamrin Wasolo; Emy Ollong; Rukiah Latuconsina; Patma Toisuta; Zainuddin Zainuddin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the application of the doctrine of participation (deelneming) to acts of abuse of authority as stipulated in Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. The research addresses the problem of whether the doctrine of participation can be applied to abuse of authority offenses, particularly given the differing qualities and authorities among actors in corruption cases. Using a normative juridical method with philosophical, statutory, conceptual, and case approaches, this study analyzes primary and secondary legal materials through qualitative and comprehensive analysis. The findings reveal that courts often fail to distinguish between principal perpetrators and participants in corruption cases, treating all actors equally despite their differing roles and authorities. The research demonstrates that the application of participation doctrine in corruption offenses requires consideration of each actor's authority, whether obtained through attribution, delegation, or mandate. The study concludes that the doctrine of participation can be applied to abuse of authority offenses by distinguishing between principal perpetrators and participants based on their respective roles and legal authority, thereby enabling proportional sentencing that reflects the degree of culpability of each actor.